2018
DOI: 10.5812/ijcm.66567
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Involvement of Axillary Lymph Nodes with Ki-67 Expression in Patients with Breast Cancer

Abstract: Background: Breast cancer is the first leading cause of cancer-related deaths in women. Ki-67 is being used for evaluation of the prognosis of patients with breast cancer. Objectives: The aim of the current study was to explore the association of the involvement of axillary lymph nodes status with the expression of Ki-67 in patients with breast cancer. Methods: A total of 449 patients were enrolled followed by evaluation of the association of Ki67 levels with demographic, pathologic, and survival data of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
1
Order By: Relevance
“…Controversial outcomes exist in literature regarding the association between lymph node metastasis and Ki-67 expression level. Findings that are opposite to ours were reported by some studies [ 42 , 48 , 49 ], and no association could be found in other studies [ 45 , 46 , 50 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Controversial outcomes exist in literature regarding the association between lymph node metastasis and Ki-67 expression level. Findings that are opposite to ours were reported by some studies [ 42 , 48 , 49 ], and no association could be found in other studies [ 45 , 46 , 50 ].…”
Section: Discussioncontrasting
confidence: 99%